Effect of Mastery Method in Learning Skill Scoring roller in football for First-Year Students - Mohamed, Zahir Mohamed Hasan (International Journal of Psychosocial Rehabilitation, 2020)
As the process of delivering information from the teacher to the student affected to some extent large methods that followed the teacher being in charge of the process of educational matter which requires the selection careful of the way a and method including consistent and capabilities of the learners so that can achieve a preferred results pestilence less effort and time is shorter as much as possible. It is through the lectures first stage appeared there decrease in the level of skill of the game of football at the students stage, whether it was that at the level he studied education sports, it which made the difficult access to achieve the only scorer of educational and educational set curriculum may be so because of their use of the method taken from by the teacher) only ordered (which is not in line with the methods of modern that of would improve the level of skill). So sees the researcher importance of using the methods of a new response reaction to the failure happening in an environment of education and in accordance with the trends of educational modern , and he has hired a researcher fashioned way Alatghani have yielded the results of this study in the E. singing process of the teaching of where to gain time in the process of learning and mastering the student skill subject of study leading to A better level of performance in order to be able to face the practical reality in society. Items of perfect Learning Consists of entrance learning from Elements Coming: Objectives Selected Clear So Should that remember Objectives in a way Clear in a Start- Process Learning. Test Codified For the learner and he Decide the level Present Learn requester Than Makes It is possible- Put it in a the place the correct From a path Learning And Provide Materials Learning Effective . Teaching in a Which Form Designer to learn From Yes Workmanship